External behavior of small states in light of theories of international relations - Abdelraouf Mostafa Galal (Review of Economics and Political Science (REPS), 2020)
Purpose - This paper aims to examine the hypotheses of main international theories (realism, liberalism and constructivism) and the development of these theories toward the behavior of foreign policy of small states in the developing world. The theories of international relations, especially the realistic theory, face a theoretical debate and a fundamental criticism. The hypotheses of these theories are not able to explain the external behavior of some small states, especially those in the developing world such as Qatar. In particular, these small states do not have the elements of physical power through which they can play this role. However, they are based on the internal determinants (such as political leadership and the variable of perception) and non-physical dimensions of power to play an effective and influential external role. Design/methodology/approach - This topic sheds light on the hypotheses of theories of main international relations, which explain the behavior of foreign policy of small states. This is due to the increased number of such states after the disintegration of Soviet Union, the practice of some countries an effective foreign role and the transformation of the concept of power from the hard power to soft power, and then to smart power Findings - The theories of international relations, especially the realistic theory, face a theoretical debate and a fundamental criticism. The hypotheses of these theories are not able to explain the external behavior of some small states, especially those in the developing world such as Qatar. In particular, these small states do not have the elements of physical power through which they can play this role. However, they are based on the internal determinants (such as political leadership and the variable of perception) and non-physical dimensions of power to play an effective and influential external role. Originality/value - The importance of the study comes from its interest in small countries in general and the Qatar situation in particular. The small country emerged as a player independent of the Gulf Cooperation Council, unlike what prevailed before, which led to the discussion of a regional role for Qatar despite its small power compared to the strength and size of other factions in the region such as Turkey, Israel and Iran.
Keywords: 330; International relations; Liberalism; Constructivism; Realism; Small states